Singapore : the future project cargo hub of Southeast Asia. Part II : characteristics of project cargo hub/trends in heavy lift shipping - Soh, Yan Zhang. (2013)
This report is an explorative study on the desirable characteristics of project cargo hubs and the trends in heavy lift shipping. The author suggests that Singapore, in the heart of Southeast Asia, stands to capitalize on the rapid development of the region if she is able to position itself as a project cargo hub. To explore Singapore’s potential as the project cargo hub of Southeast Asia, there is a need to identify the major project cargo hubs in the world and the desirable characteristics of these hubs. The trends and future of heavy lift shipping were also investigated as market-changing trends may make or break the development of a project cargo hub. Finally, a brief analysis of Singapore’s potential as a project cargo hub was carried out by looking at Singapore’s strengths and constraints as a project cargo hub and how the trends in heavy lift shipping may impact Singapore.